Update to the catalogue of South Australian freshwater fishes (Petromyzontida & Actinopterygii) - Hammer, Michael P.; Adams, Mark; Foster, Ralph (Zootaxa, 2012)
South Australia is a large Australian state (~1,000,000 km2) with diverse aquatic habitats spread across temperate to arid environments. The knowledge of freshwater fishes in this jurisdiction has advanced considerably since the last detailed catalogue of native and alien species was published in 2004 owing to significant survey and research effort, spatial analysis of museum data, and incidental records. The updated list includes 60 native and 35 alien species. New additions to the native fauna include cryptic species of Retropinna semoni s.l. (Weber) and Galaxias olidus s.l. (Günther). Two others have been rediscovered after long absences, namely Neochanna cleaveri (Scott) and Mogurnda adspersa (Castelnau). Range extensions are reported for native populations of Galaxias brevipinnis Günther, Leiopotherapon unicolour (Günther), Hypseleotris spp. (hybridogenetic forms) and Philypnodon macrostomus Hoese and Reader. There are five new alien species records (all aquarium species) including Phalloceros caudimaculatus (Hensel), Poecilia reticulata Peters, Xiphophorus hellerii Heckel, Astronotus ocellatus (Agassiz) and Paratilapia polleni Bleeker, with confirmation of Misgurnus anguillicaudatus (Cantor). Other range extensions for alien (exotic or translocated native) species in different drainage divisions (various modes of human-mediated dispersal) include Nematalosa erebi (Günther), Cyprinus carpio Linnaeus, Oncorhynchus mykiss (Walbaum), Salmo salar Linnaeus, Salvelinus fontinalis (Mitchell), Melanotaenia fluviatilis (Castelnau), Atherinosoma microstoma (Günther), Macquaria novemaculeata (Steindachner), Nannoperca australis Günther, Pseudaphritis urvillii (Valenciennes), and Hypseleotris spp. (hybridogenetic forms). New records are a combination of greater available information and new incursions, highlighting the need for ongoing detailed surveys and reporting to detect rare native and alien species.